Defining Academic Freedom: How Statewide Political Turmoil Shaped the Debate on Academic Freedom at the University of Wisconsin in 1910 - Castillo, Nathan G. (My University, 2013)
This thesis revisits the events of 1910 spring semester at the University of Wisconsin detailed in "Sifting and Winnowing: A chapter in the History of Academic Freedom at the University of Wisconsin," about the famous Sifting and Winnowing plaque. It is a larger study on the process of defining academic freedom in 1910. This thesis contends that the plaque was not the center of debate on academic freedom in 1910 as "Sifting and Winnowing" suggested. Additional material has been included that demonstrates discussions of academic freedom occurred simultaneously to and independently of the plaque. Although the plaque contributed to the process of defining academic freedom, the driving force was statewide political turmoil caused by tensions between Stalwart and Progressive Republicans. The scope of this study includes discussions on academic freedom between the university community, Board of Regents, and journalists during the months before and after the 1910 spring semester. By focusing on the spring semester as a whole, rather than just on the plaque, it becomes evident that discussions over academic freedom occurred during an institutional conflict between the Regents and the university community about political activity within the university. Moreover, a larger statewide political conflict circumscribed these interactions. These elements overshadowed the significance of the plaque at the time. Therefore, this thesis focuses on the 1910 spring semester as a whole, putting the discussions on academic freedom in the context of statewide politic tensions that found their way into the university.
Keywords: University of Wisconsin -- History; University of Wisconsin -- Political activity -- History; Academic freedom -- Wisconsin -- History; Higher education and state -- Wisconsin -- History; Wisconsin -- Politics and government -- 1848-1950